A Review of Potential Marine-derived Hypotensive and Anti-obesity Peptides. Issue 1 (2nd January 2016) - Manikkam, V.; Vasiljevic, T.; Donkor, O. N.; Mathai, M. L.
Abstract : Bioactive peptides are food derived components, usually consisting of 3–20 amino acids, which are inactive when incorporated within their parent protein. Once liberated by enzymatic or chemical hydrolysis, during food processing and gastrointestinal transit, they can potentially provide an array of health benefits to the human body. Owing to an unprecedented increase in the worldwide incidence of obesity and hypertension, medical researchers are focusing on the hypotensive and anti-obesity properties of nutritionally derived bioactive peptides. The role of the renin–angiotensin system has long been established in the aetiology of metabolic diseases and hypertension. Targeting the renin–angiotensin system by inhibiting the activity of angiotensin-converting enzyme (ACE) and preventing the formation of angiotensin II can be a potential therapeutic approach to the treatment of hypertension and obesity. Fish-derived proteins and peptides can potentially be excellent sources of bioactive components, mainly as a source of ACE inhibitors. However, increased use of marine sources, poses an unsustainable burden on particular fish stocks, so, the underutilized fish species and by-products can be exploited for this purpose. This paper provides an overview of the techniques involved in the production, isolation, purification, and characterization of bioactive peptides from marine sources, as well as the evaluation of the ACE inhibitory (ACE-I) activity and bioavailability.